salut
je veux d'aide pour factoriser ces 2 expressions
B(x)=(5x+10)(2x−5)−(x+3)2
R(x)=(7x−7)(2x−9)−(4−4x)(5x+1)


Sagot :

Bonjour,

Factoriser:

  • B(x)= (5x+10)(2x−5)−(x+3)²

B(x)= 10x²+20x-25x-50-x²-6x-9

B(x)= 9x²-11x-59

Δ= (-11)²-4(9)(-59)= 2245 > 0; 2 solutions

x1= (-(-1)-√2245)/2(9)= (11-√2245)/18

x2= (-(-1)+√2245)/2(9)= (11+√2245)/18

B(x)= (x- (11-√2245)/18))(x-  (11+√2245)/18))

  • R(x)=(7x−7)(2x−9)−(4−4x)(5x+1)

R(x)= 7(x-1)(2x-9)-4(1-x)(5x+1)

R(x)= 7(x-1)(2x-9) + 4(x-1)(5x+1)   ***changement de signe

R(x)= (x-1)(7(2x-9+4(5x+1))

R(x)= (x-1)(14x-63+20x+4)

R(x)= (x-1)(34x-59)